2018
DOI: 10.1021/acssensors.7b00920
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica Thin Films for Improved Electrochemical Detection of Paraquat

Abstract: An electrochemical method was developed for rapid and sensitive detection of the herbicide paraquat in aqueous samples using mesoporous silica thin film modified glassy carbon electrodes (GCE). Vertically aligned mesoporous silica thin films were deposited onto GCE by electrochemically assisted self-assembly (EASA). Cyclic voltammetry revealed effective response to the cationic analyte (while rejecting anions) thanks to the charge selectivity exhibited by the negatively charged mesoporous channels. Square wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
128
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 135 publications
(130 citation statements)
references
References 68 publications
(124 reference statements)
2
128
0
Order By: Relevance
“…Surfactant-containing films have been used as permselective sensors for lipophilic analytes (e. g., pharmaceutical drugs [17] or trace nitroaromatic explosives and pesticides [18]) based on their extraction in the surfactant phase and subsequent detection onto the electrode surface while rejecting ionic interferences [19]. Applications of surfactant-extracted films include preconcentration electroanalysis of redox cations (via electrostatic binding to the negatively charged silica surface) [20,21], permselective coatings (based on charge selectivity [22], hydrophobic/ hydrophilic balance [23] or gated molecular transport [24]), or molecular sieving membranes [25] which are also likely to be exploited as antifouling surfaces [26]. Oriented mesoporous silica films bearing organo-functional groups can be also prepared [27].…”
Section: Critical Effect Of Film Thickness On Preconcentration Electrmentioning
confidence: 99%
See 3 more Smart Citations
“…Surfactant-containing films have been used as permselective sensors for lipophilic analytes (e. g., pharmaceutical drugs [17] or trace nitroaromatic explosives and pesticides [18]) based on their extraction in the surfactant phase and subsequent detection onto the electrode surface while rejecting ionic interferences [19]. Applications of surfactant-extracted films include preconcentration electroanalysis of redox cations (via electrostatic binding to the negatively charged silica surface) [20,21], permselective coatings (based on charge selectivity [22], hydrophobic/ hydrophilic balance [23] or gated molecular transport [24]), or molecular sieving membranes [25] which are also likely to be exploited as antifouling surfaces [26]. Oriented mesoporous silica films bearing organo-functional groups can be also prepared [27].…”
Section: Critical Effect Of Film Thickness On Preconcentration Electrmentioning
confidence: 99%
“…Finally, free-standing mesoporous silica membranes can be used for molecular filtration [34]. In a previous work [21], we have shown that perpendicularly oriented mesoporous silica thin films electrogenerated by EASA on glassy carbon electrode can be successfully applied to the preconcentration electroanalysis of paraquat, a cationic 4,4'-bipyridinium-based pesticide likely to bind quickly to the negatively charged silica surface. Here we discuss the critical effect of film thickness of the sensor's sensitivity, on the basis of deposits obtained after distinct synthesis durations.…”
Section: Critical Effect Of Film Thickness On Preconcentration Electrmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, nanoporous gold electrodes have been employed for the detection of DNAs in diluted biofluids . SNM modified electrodes have also illustrated excellent antifouling ability and allowed the direct detection of a variety of targets in complex samples and rat brain with high sensitivities . Our previous study shows that the SNM modified carbon fiber microelectrode (SNM/CFME) can work stably in rat brain up to 2 h .…”
Section: Introductionmentioning
confidence: 99%